Effect of oral supplementation of probiotic strains of Lactobacillus rhamnosus and Enterococcus faecium on the composition of the faecal microbiota of foals. Issue 3 (10th March 2019) - Urubschurov, Vladimir; Stroebel, Christina; Günther, Elena; Romanowski, Kristin; Büsing, Kirsten; Zeyner, Annette
Abstract: Effects of probiotics on the intestinal microbiota of foals are yet insufficiently studied. The aim of this study was to investigate whether supplementation of Lactobacillus rhamnosus (DSM 7133) and Enterococcus faecium (DSM 7134) influences the bacterial composition of the faecal microbiota of foals. A total of 34 newborn foals were randomly assigned to the placebo group (PG, n  = 16) and the treatment group (TG, n  = 18). From day 1 to day 14 of life, foals orally received 3 ml of either a probiotic preparation (1.05 × 10 9 CFU E. faecium and 4.50 × 10 8 CFU L. rhamnosus ) or placebo (carrier) once a day. Faeces were collected directly from the rectum immediately after birth (meconium) and at day 14 and day 56 of life. Samples of 12 foals per group were selected for microbiological analysis. DNA was extracted and used for polymerase chain reaction–denaturing gradient gel electrophoresis (PCR‐DGGE) and quantitative PCR. No DNA or amplicons were obtained from meconium. There were no differences in richness of bands and Shannon index of diversity regarding the Clostridium cluster XIVa between groups. Cluster analysis and principal coordinate analysis of DGGE data showed a clear effect of age. Band‐based similarity of bacterial clusters (Dice coefficient) decreased from day 14 to day 56 of life ( p  < 0.001) in PG foals only resulting in lower similarity in PG versus TG foals when 2 month old ( p  < 0.01). Five of thirty re‐amplified bands were identified on species level. Others were assigned either to family (mainly Lachnospiraceae ) or genus level ( Akkermansia ). The bands related to Akkermansia muciniphila or Akkermansia spp. appeared almost in all DGGE profiles. Two‐week supplementation of the probiotic preparation to foals had no significant impact on the composition of the faecal microbiota but it appears to have prevented the reduction of bacterial similarity between 2 and 8 weeks of age observed in not treated foals.